기계적 합금화를 이용한 Al0.75V2.82CrZr 내화 고엔트로피 합금의 경량화 및 고온 열안정성 연구 - 김민수; 이한성; 안병민 (한국분말재료학회지, 2023)
High-entropy alloys (HEAs) are characterized by having five or more main elements and forming simple solids without forming intermetallic compounds, owing to the high entropy effect. HEAs with these characteristics are being researched as structural materials for extreme environments. Conventional refractory alloys have excellent hightemperature strength and stability; however, problems occur when they are used extensively in a high-temperature environment, leading to reduced fatigue properties due to oxidation or a limited service life. In contrast, refractory entropy alloys, which provide refractory properties to entropy alloys, can address these issues and improve the hightemperature stability of the alloy through phase control when designed based on existing refractory alloy elements. Refractory high-entropy alloys require sufficient milling time while in the process of mechanical alloying because of the brittleness of the added elements. Consequently, the high-energy milling process must be optimized because of the possibility of contamination of the alloyed powder during prolonged milling. In this study, we investigated the hightemperature oxidation behavior of refractory high-entropy alloys while optimizing the milling time.
Keywords: Refractory alloy; High entropy alloy; Oxidation behavior; Mechanical alloying; Powder metallurgy